A uracil nitroso amine based colorimetric sensor for the detection of Cu2+ ions from aqueous environment and its practical applications. Issue 28 (24th February 2015) - Patil, Samadhan R.; Nandre, Jitendra P.; Patil, Prashant A.; Sahoo, Suban K.; Devi, Manisha; Pradeep, Chullikkattil P.; Fabiao, Yu; Chen, Lingxin; Redshaw, Carl; Patil, Umesh D.
Abstract : Uracil nitroso amine based colorimetric chemosensor for Cu 2+ ions from a 100% aqueous environment. Abstract : A simple uracil nitroso amine based colorimetric chemosensor (UNA-1 ) has been synthesized and screened for its cation recognition ability. SensorUNA-1 exhibited a high sensitivity and selectivity towards Cu 2+ ions in aqueous medium in the presence of a wide range of other competing cations (Ag +, Al 3+, Ba 2+, Ca 2+, Cd 2+, Co 2+, Cr 3+, Cs +, Fe 2+, Fe 3+, Li +, Mg 2+, Mn 2+, Na +, Ni 2+, Pb 2+, Zn 2+, Hg 2+ and Sr 2+ ). With Cu 2+, the sensorUNA-1 gave a distinct color change from colorless to dark yellow by forming a complex of 1 : 1 stoichiometry. Furthermore, sensorUNA-1 was successfully utilized in the preparation of test strips and supported silica for the detection of Cu 2+ ions from aqueous environment.